Autosomal mutations affecting adhesion between wing surfaces in Drosophila melanogaster. - Prout, M.; Damania, Z.; Soong, J.; Fristrom, D.; Fristrom, J.W. (Genetics, 1997)
Integrins are evolutionarily conserved transmembrane alpha,beta heterodimeric receptors involved in cell-to-matrix and cell-to-cell adhesions. In Drosophila the position-specific (PS) integrins mediate the formation and maintenance of junctions between muscle and epidermis and between the two epidermal wing surfaces. Besides integrins, other proteins are implicated in integrin-dependent adhesion. In Drosophila, somatic clones of mutations in PS integrin genes disrupt adhesion between wing surfaces to produce wing blisters. To identify other genes whose products function in adhesion between wing surfaces, we conducted a screen for autosomal mutations that produce blisters in somatic wing clones. We isolated 76 independent mutations in 25 complementation groups, 15 of which contain more than one allele. Chromosomal sites were determined by deficiency mapping, and genetic interactions with mutations in the beta PS integrin gene myospheroid were investigated. Mutations in four known genes (blistered, Delta, dumpy and mastermind) were isolated. Mutations were isolated in three new genes (piopio, rhea and steamer duck) that affect myo-epidermal junctions or muscle function in embryos. Mutations in three other genes (kakapo, kiwi and moa) may also affect cell adhesion or muscle function at hatching. These new mutants provide valuable material for the study of integrin-dependent cell-to-cell adhesion.